ANALISIS HARGA SAHAM PADA PERUSAHAAN SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nadhifah (2021)
This study aimed to assess the effect of Probability, Liquidity and Leverage on Stock Price. The population is all Miscellaneous Industry Sector Companies Listed in Indonesia Stock Exchange. By using Purposive Sampling method, obtained 22 companies in the Miscellaneous Industry Sector with a research period of four years to obtain 88 data. Data analysis technique by using Panel Data Regression Analysis with Eviews 11 and significant 5%. This study shows the results that profitability as measured by Return on Equity (ROE) has a positive effect on Stock Price, Liquidity as measured by Current Ratio (CR) has no effect on Stock Price and Leverage as measured by Debt to Equity Ratio (DER) has a positive effect on Stock Price.